The influence of 4G/5G polymorphism in the plasminogen-activator-inhibitor-1 promoter on COVID-19 severity and endothelial dysfunction - Yatsenko, Tetiana; Rios, Ricardo; Nogueira, Tatiane; Salama, Yousef; Takahashi, Satoshi; Adachi, Eisuke; Tabe, Yoko; Hattori, Nobutaka; Osada, Taro; Naito, Toshio; Takahashi, Kazuhisa; Hattori, Koichi; et al. (Frontiers in Immunology, 2024)
Plasminogen activator inhibitor-1 (PAI-1) is linked to thrombosis and endothelial dysfunction in severe COVID-19. The +43 G>A PAI-1 and 4G/5G promoter polymorphism can influence PAI-1 expression. The 4G5G PAI-1 promoter gene polymorphism constitutes the 4G4G, 4G5G, and 5G5G genotypes.However, the impact of PAI-1 polymorphisms on disease severity or endothelial dysfunction remains unclear. Clinical data, sera, and peripheral blood mononuclear cells (PBMCs) of COVID-19 patients were studied. Comorbidities and clinical biomarkers did not correlate with genotypes in either polymorphism. However, differences between fibrinolytic factors and interleukin-1 (IL-1) were identified in genotypes of the 4G/5G but not the 43 G>A PAI polymorphism. Patients with the 4G4G genotype of the 4G/5G polymorphism showed high circulating PAI-1, mainly complexed with plasminogen activators, and low IL-1 and plasmin levels, indicating suppressed fibrinolysis. NFB was upregulated in PBMCs of COVID-19 patients with the 4G4G genotype.Mechanistically, IL-1 enhanced PAI-1 expression in 4G4G endothelial cells, preventing the generation of plasmin and cleavage products like angiostatin, soluble uPAR, and VCAM1. We identified inflammation-induced endothelial dysfunction coupled with fibrinolytic system overactivation as a risk factor for patients with the 5G5G genotype.